Klebsiella pneumoniae Carbapenemase Producers in South Korea between 2013 and 2015 - Yoon, Eun-Jeong; Kim, Jung Ok; Kim, Dokyun; Lee, Hyukmin; Yang, Ji Woo; Lee, Kwang Jun; Jeong, Seok Hoon (Frontiers in Microbiology, 2018)
Between 2014 and 2015, the Klebsiella pneumoniae carbapenemase (KPC) was becoming endemic in South Korea. To assess this period of transition, we analyzed KPC producers in terms of molecular epidemiology. A total of 362 KPC-producing Enterobacteriaceae strains, including one from 2013, 13 from 2014, and 348 from 2015, were actively collected from 60 hospitals throughout the peninsula. Subtypes of KPC were determined by PCR and direct sequencing, and isotypes of Tn4401 (the transposon flanking the blaKPC gene) were specified by PCR using isotype-specific primers and direct sequencing. Sporadic occurrence of KPC-producing Enterobacteriaceae was initially observed around Seoul, which is the most crowded district of the country, and these strains rapidly disseminated in 2014, to the other parts of the country in 2015. The bacterial clones responsible for the extreme epidemiological transition were K. pneumoniae ST307 (46.2%) and ST11 (21.3%). Less frequently, E. coli (4.7%), Enterobacter spp. (1.4%), and other Enterobacteriaceae members (1.7%) producing the enzyme were identified. The blaKPC-2 gene bracketed by Tn4401a (72.1%) was the most prevalent mobile genetic element responsible for the dissemination, and the same gene carried either by Tn4401b (2.2%) or Tn4401c (6.6%) was identified at a lesser frequency. The genes blaKPC-3 (1.6%) and blaKPC-4 (6.4%), both flanked by Tn4401b, were occasionally identified. This study showed endemic dissemination of KPC producers in 2015 due to a clonal spread of two K. pneumoniae strains. Further systemic surveillance is needed to monitor dissemination of KPC-producers.